2015
DOI: 10.1002/art.39065
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Abnormalities in Adjuvant‐Induced Arthritis: Relationship to Macrovascular Endothelial Function and Markers of Endothelial Activation

Abstract: Objective. To determine the time course of microvascular abnormalities and the link with macrovascular endothelial function and circulating markers of endothelial activation in adjuvant-induced arthritis (AIA) in rats.Methods. Microvascular function/structure and mechanics were studied in third-order mesenteric arteries subjected to flow and/or pressure on day 4 (preclinical arthritis), day 11 (very early arthritis), day 33 (severe disease), and day 90 (when inflammation has resolved) after AIA induction. Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 49 publications
4
33
0
Order By: Relevance
“…These discrepant results may be explained by the great heterogeneity in RA disease stage, dosages and treatment duration of GCs, or therapies Glucocorticoids and endothelial function in arthritis V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 188: 208-218 associated with GCs among these studies. These data corroborate the seminal role of the balance between COX-2 and NOS/arginase pathways in endothelial dysfunction identified previously in AIA [24], and demonstrate that the positive effect of GCs on endothelial function requires a combination of concomitant effects on NOS, arginase, COX-2 and O -2 8 pathways, as observed previously with other drugs such as arginase inhibitors or etanercept [18,24]. In our conditions, the HD of prednisolone was associated with a negative effect on cardiometabolic parameters, such as blood pressure and lipid levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These discrepant results may be explained by the great heterogeneity in RA disease stage, dosages and treatment duration of GCs, or therapies Glucocorticoids and endothelial function in arthritis V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 188: 208-218 associated with GCs among these studies. These data corroborate the seminal role of the balance between COX-2 and NOS/arginase pathways in endothelial dysfunction identified previously in AIA [24], and demonstrate that the positive effect of GCs on endothelial function requires a combination of concomitant effects on NOS, arginase, COX-2 and O -2 8 pathways, as observed previously with other drugs such as arginase inhibitors or etanercept [18,24]. In our conditions, the HD of prednisolone was associated with a negative effect on cardiometabolic parameters, such as blood pressure and lipid levels.…”
Section: Discussionsupporting
confidence: 91%
“…AIA model [19,[22][23][24]) thoracic aorta was excised, cleaned of connective tissue and cut into rings $2 mm in length. Rings were suspended in Krebs solution (mol/l: NaCl 118, KCl 4Á65, CaCl 2 2Á5, KH 2 PO 4 1Á18, NaHCO 3 24Á9, MgSO 4 1Á18, glucose 12, pH 7Á4), maintained at 378C and aerated continuously with 95% O 2 , 5% CO 2 for isometric tension recording in organ chambers.…”
Section: Tissue Collection Blood Pressure and Heart Rate Measurementsmentioning
confidence: 99%
“…Thus, edema in association with the reduction in body mass shows the effectiveness of the AIA induction protocol used. Moreover, edema occurred also in the contralateral hind paws in relation to the administration of the adjuvant, thereby indicating the polyarticular characteristic of the employed model (Totoson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, previous studies demonstrated that the AIA‐induced joint inflammatory process is transitory and self‐limited (Totoson et al ., ). In this manner, the hypoandrogenism could occur in an earlier phase of the AIA model, when the joint inflammatory process is more active (Clemens & Bruot, ; Carageorgiou et al ., ; Darwish et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In an experimental study, it has been shown that microvascular endothelial dysfunction occurred earlier than macrovascular endothelial dysfunction in rats with adjuvant-induced arthritis (43). In a prospective cohort study, microvascular disease was observed to be a predictor for the development of major peripheral artery disease during a 5-year follow-up in patients with type 2 diabetes (42).…”
Section: Discussionmentioning
confidence: 99%